ANALYSIS OF CATEGORY SHIFT ON EMMA HEESTERS’S COVER SONG LYRICS ON YOUTUBE - Wisnu Sanjaya; Baharuddin; Lalu Jaswadi Putera; Lalu Ali Wardana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to Analyze and Categorize the types of category shift that occur in the English version of Indonesian Song’s lyrics covered by Emma Heesters. This research was Descriptive Qualitative Research method and catford (1965)translation shift theory was caried in this study . The sample of this research was the lyrics which consist in 7 Song’s of her cover . The data of the research take on Emma Heester Youtube chanel. Based on Catford''s theory as the foundation of this reserach , a total of 189 data were found across 7 songs covered by Emma Heesters. Structure Shift emerged significantly, reaching 20.11%, Intra System Shift, representing 15.87%, . Conversely, Class Shift appeared with the lowest frequency at 5.82%,. Among the identified categories, Unit Shift emerged as the most dominant, constituting 58.20% of the dataset. In summary, the study revealed the dominance of Unit Shift in these translations, highlighting the complexity of adapting song lyrics, including stylistic, rhyme and rhythm consideration and emotional elements, to a different language.